Penggunaan Media Quizizz Berbantuan Game Paper Mode Untuk Meningkatkan Motivasi Belajar Bahasa Indonesia Siswa Kelas IV SD Inpres 12/79 Matuju Kabupaten Bone - Sudirman; Abd. Hafid; Satriani; Risnarita Rahmiati (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aimed to describe the use of Quizizz media assisted by Game Paper mode in improving the learning motivation of fourth-grade students at SD Inpres 12/79 Matuju, Bone Regency. This research employed a descriptive qualitative approach with Classroom Action Research (CAR) as the research design. The subjects of the study consisted of all 13 fourth-grade students and the classroom teacher. The research instruments included observation sheets and student learning motivation questionnaires. Data were collected through observation and questionnaires, while data analysis techniques involved data reduction, data presentation, and conclusion drawing. The results showed that the use of Quizizz assisted by Game Paper mode improved students’ learning motivation. This was indicated by the increase in teacher activity from 72.22% in Cycle I, categorized as good, to 94.44% in Cycle II, categorized as very good. In addition, the average score of students’ learning motivation increased from 1.6 in Cycle I, categorized as low, to 3.4 in Cycle II, categorized as high. It can be concluded that the use of Quizizz media assisted by Game Paper mode effectively improved the learning motivation of fourth-grade students at SD Inpres 12/79 Matuju, Bone Regency.